Peran Auditor Internal dalam Tahap Implementasi dan Evaluasi sistem ERP: Integrasi Framework COBIT 5 (Studi Kasus Pada PT Astra International Tbk - Honda Sales Operation): Studi Kasus pada PT. Astra International, Tbk – Honda Sales Operation - Suwan Li; Mega Handayani; Inna Zahara (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
Internal auditors play a role in providing confidence in the effectiveness of internal control in order to achieve an organization's goals. Developing a company's ERP system is a process that needs to involve the function of the internal auditor. Astra Motor, one of the operational offices of PT Astra International Tbk, is transitioning the company's ERP system, which originally used the Pygmalion Synchronization System (PSS), to become the Astra Motor Integrated System (STAR). This study aims to assess the suitability of internal auditors' role in the implementation and evaluation stages of Astra Motor's ERP system. The COBIT 5 framework (ISACA 2012) guides this qualitative case study research, which uses primary data from interviews, questionnaires, and observations, positioning internal auditors as responsible (R) on the RACI chart. We used descriptive analysis as the initial analysis and applied the Dean J. Champion formula for data analysis. The results of this research show that the role of internal auditors in the implementation and evaluation stages of the ERP system is very appropriate, with an involvement percentage of 87%. The short duration of the research is a limitation faced by the researchers and a suggestion for further research. We expect future research to involve the IT team in analyzing the role of internal auditors in the implementation and evaluation stages of the ERP system.